ANALYSIS OF INSTRUCTIONAL COMMUNICATION IMPROVING STUDENT SATISFACTION WITH TEACHING QUALITY IN STUDY PROGRAM OF D4 MEETING, INCENTIVE, CONVENTION, EXHIBITION (MICE) AT MEDAN STATE POLYTECHNIC - Simbolon, Yohana Yulianti; Rizqiana, Dyah Seruni; Sembiring, Putri Sosanti; Maharani, Blangi Intan; Rahma, Annisa Dian (Universitas Riau, 2025)
This study analyse the implementation of instructional communication by lecturers and its impact on student satisfaction levels in the D4 Meeting, Incentive, Convention, and Exhibition (MICE) Study Programme at the Medan State Polytechnic. This study employs a qualitative descriptive approach, with data collected through a closed-ended questionnaire. Instructional communication plays a crucial role in developing communicators' skills to understand the ongoing learning situation and adapt teaching strategies to meet students' needs as learners. The research results indicate that instructional communication plays a very important role in enhancing student satisfaction with the quality of the learning process. Effective communication between lecturers and students, characterised by clear information delivery, the use of varied teaching methods, and the provision of constructive feedback, significantly contributes to increased student engagement and satisfaction during lectures. Some of the main challenges faced include instructors' difficulties in adapting teaching materials to the diverse backgrounds and abilities of students, as well as limited access to relevant and up-to-date reference sources in the field of MICE. These factors have the potential to reduce teaching effectiveness and, in turn, negatively impact student satisfaction if not addressed strategically.